2017
DOI: 10.1016/j.ijpharm.2017.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Development and physicochemical characterization of acetalated dextran aerosol particle systems for deep lung delivery

Abstract: Biocompatible, biodegradable polymers are commonly used as excipients to improve the drug delivery properties of aerosol formulations, in which acetalated dextran (Ac-Dex) exhibits promising potential as a polymer in various therapeutic applications. Despite this promise, there is no comprehensive study on the use of Ac-Dex as an excipient for dry powder aerosol formulations. In this study, we developed and characterized pulmonary drug delivery aerosol microparticle systems based on spray-dried Ac-Dex with cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…67,68 Spray drying has been used to produce Ac-DEX aerosol microparticles, particularly for pulmonary delivery applications. 46,47,[69][70][71][72] The microscale dry power facilitated the delivery and deposition on the mucosal layer of the lung via inhalation. 47,72 Furthermore, this technique can be used combined with single emulsion or nanoprecipitation.…”
Section: Spray Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Spray drying has been used to produce Ac-DEX aerosol microparticles, particularly for pulmonary delivery applications. 46,47,[69][70][71][72] The microscale dry power facilitated the delivery and deposition on the mucosal layer of the lung via inhalation. 47,72 Furthermore, this technique can be used combined with single emulsion or nanoprecipitation.…”
Section: Spray Dryingmentioning
confidence: 99%
“…46,47,[69][70][71][72] The microscale dry power facilitated the delivery and deposition on the mucosal layer of the lung via inhalation. 47,72 Furthermore, this technique can be used combined with single emulsion or nanoprecipitation. Specifically, drug-loaded Ac-DEX NPs were prepared by conventional oil-in-water single emulsion or nanoprecipitation first, and then spray-dried with excipients (Fig.…”
Section: Spray Dryingmentioning
confidence: 99%
“…Particle size and zeta potential results also indicated that spray-drying and freeze-drying processes did not change the physicochemical properties of NPs after re-dispersion. According to previous studies, 27 there is no notable influence on the MMAD of the particles for NPs. Therefore, after inhalation and deposition into the lungs in the form of aggregated particles, NPs could re-dissolve into their nanometer size in the aqueous surroundings on the lung epithelium, and bypass the air–blood barrier and distribute to the extra-pulmonary organs.…”
Section: Discussionmentioning
confidence: 69%
“…Acdex is composed of acyclic and cyclic acetal groups, with the acyclic acetals degrading faster than the cyclic acetal groups [17]. As a consequence, the degradation behavior of Acdex can be fine-tuned by varying the degree of substitution of the cyclic vs. acyclic acetal groups on the dextran backbone [18]. Most importantly, under slightly acidic conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%